Infection with HHV-6 of military men affected by community-acquired pneumonia - Brusnik, S; Popova, N; Popova, L (Annals of Mechnikov’s Institute, 2020)
Human herpesvirus, 6 type (HHV-6) was isolated at the end of the 20th century from the blood leukocytes of patients with lymphoproliferative diseases. Serological studies conducted in different countries, indicate ubiquitylation of the HHV-6 and the existence of two antigenic variants - HHV-6A and HHV-6B. Their high tropism is determined in vitro to lymphocytic, nervous and dendritic cells of the CNS. Virus replicates in many cell, primary and passaged cultures of different origins. The reproduction cycle of HHV-6 continues on average 4-5 days forming syncytiums and intracytoplasmic and intranuclear inclusions. Significant destruction and lysis almost 90 % of infected cells is reported after 5-10 day of monitoring. The utility of experimentation investigating the role of HHV-6 in the development of acute and chronic diseases in respiratory tract is caused by the fact that many patients, particularly those with chronic diseases, have complaints to chronic fatigue, decreased performance and low-grade temperature more than 3-6 months. Several studies demonstrate the presence of HHV-6 in saliva, salivary and bronchiolar glands, in swabs from pharyngonasal cavity and gorge. Tropism of HHV-6 to oropharyngeal epithelium with the possibility of finding the virus in the saliva and swabs from pharyngonasal cavity and gorge was found at the end of 20th century. This fact gave the basis for work determining the level of infection by this pathogen in patients with infectious and inflammatory pathology of the respiratory tract. Materials and methods. Serological studies were conducted with 38 soldiers affected by community-acquired pneumonia. Most of the surveyed patients were ranged in age from 20 to 45 years old, middle age (32,5±1,5) years. Patients were in stationary treatment in the Kharkov military hospital. The criteria for inclusion in the study on the infection of HHV-6 were soldiers affected by community-acquired pneumonia with atypical course of disease. Some patients have short-term (1-2 days), macular papulose eruption on hands and legs, prolonged low-grade fever, chronic fatigue. The control group included 18 apparently healthy persons. Enzyme immune analysis (EIA) using commercial diagnostic system "VektoHHV-6-IgG» was applied to determine the immunoglobulin class G (IgG) for HHV-6 in serum and saliva of the examined. Registration of the EIA results was performed using spectrophotometer StatFax 303 by determining the optical density (OD) in optical experimental values and control samples of blood serum and saliva. Result evaluation is carried out in accordance with requirements stated in the instructions to the test system with obligatory consideration of anamnestic and clinical data from the examined patients. Results and discussion. The above data show that among the examined patients’ infection with HHV-6 was 26,3 % of apparently healthy persons in the control group, this figure was 2 times lower than 10,5%. In saliva of the CAP patients as well as in blood and serum was found IgG to HHV-6. One patient from IgG to HHV-6 control group have been identified in saliva and serum. The results of the research allowed establishing the level of seropositive individuals to HHV-6 and demonstrate the ability to diagnosis HHV-6 infection in infectious and inflammatory processes of the respiratory tract. Conclusion. The studies have shown the use of saliva as an object of study for the establishment markers of HHV-6 in patients affected by CAP with important advantage - non-invasive receiving of material from patients for laboratory diagnosis. It can be assumed that high level of infection for patients affected by CAP is associated with ease droplet spread of herpesvirus through saliva.